FROM PLAY TO PURCHASE: HOW GAMIFICATION EXPERIENCE DRIVES PURCHASE INTENTION THROUGH TRUST, VALUE, AND ENGAGEMENT - Advent Chandra; Deverrel Ryanvianda; Hotlan Siagian (Petra Christian University, 2026)
This study aims to examine the influence of gamification experience on purchase intention, with perceived trust, perceived value, and customer engagement as mediating variables, among Shopee e-commerce users in East Java Province. This study uses a quantitative approach, with numerical scale data collected via an online questionnaire in Google Forms. The research population comprises individuals in East Java who have used Shopee and made transactions on it. The sampling technique used was nonprobability judgmental sampling, with the criteria that respondents were at least 17 years old and had made transactions in the last three months. A total of 200 respondents met the criteria and were analyzed in this study. All measurement items were graded using a five-point Likert scale, ranging from 1 (strongly disagree) to 5 (strongly agree). Data analysis was carried out using descriptive statistics and Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The results show that gamification experience has a significant effect on perceived trust, perceived value, and customer engagement, with the strongest influence on customer engagement. However, the gamification experience does not have a significant direct effect on purchase intention. In addition, perceived value and customer engagement have a significant effect on purchase intention, whereas perceived trust does not. Mediation analysis showed that perceived value and customer engagement mediated the relationship between gamification experience and purchase intention, whereas perceived trust did not. These findings confirm that engagement-based mechanisms and value perceptions are more decisive in translating gamification experiences into purchase intent than trust alone, thereby expanding the theoretical understanding of gamification's effectiveness in the context of digital commerce.